1999
DOI: 10.1097/00006123-199904000-00062
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy: Outcome Analysis of 100 Consecutive Procedures

Abstract: ETV is most effective in treating uncomplicated occlusive hydrocephalus caused by aqueductal stenosis and space-occupying lesions. ETV is still effective in two-thirds of the patients with previous infections or intraventricular bleeding. Patients who have previously undergone shunting and who have occlusive hydrocephalus should undergo ETV at the time of shunt failure, with immediate ligation or removal of the shunt device. In selected cases of distorted anatomy or impaired visual conditions, stereotactic gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
268
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(288 citation statements)
references
References 32 publications
14
268
1
4
Order By: Relevance
“…ETV has been reported to be effective in the treatment of hydrocephalus with success rates ranging between 49 and 100%, depending on the aetiology of hydrocephalus, the criteria used for patient selection, and the follow-up period [2, 3, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. Despite these encouraging reports, most authors have suggested that the outcome following ETV is significantly worse in children less than 1 year old as compared with older children [4, 10, 16, 17, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ETV has been reported to be effective in the treatment of hydrocephalus with success rates ranging between 49 and 100%, depending on the aetiology of hydrocephalus, the criteria used for patient selection, and the follow-up period [2, 3, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. Despite these encouraging reports, most authors have suggested that the outcome following ETV is significantly worse in children less than 1 year old as compared with older children [4, 10, 16, 17, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Initially reported to work best in patients with late-onset aqueduct stenosis (AS), endoscopic third ventriculostomy (ETV) is now used in many centres for a wider variety of indications with varying success rates, depending on the aetiology of the hydrocephalus and the patient’s age [1, 2, 3, 4]. Despite the excellent results achieved in adults and older children, the reported outcome of ETV in children less than 1 year old has been disappointing, with success rates ranging between 0 and 23% [2, 5]. The aims of this study were to evaluate the role of ETV as a primary treatment for hydrocephalus in infants and to determine its impact as a whole on the reduction of cerebrospinal fluid (CSF) shunts necessary in a new population of hydrocephalic infants.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) flow restoration is done by a variety of endoscopic techniques including ETV, aqueductoplasty, aqueduct stenting, septostomy, Monroplasty, and removal/decompression of CSF flow-obstructing mass lesions [3]. Basically, the technique of ETV involves telescope insertion through the lateral ventricle, into the third ventricle and perforating the third ventricular floor over the premamillary region by various techniques [4]. …”
Section: Introductionmentioning
confidence: 99%
“…The refinement of endoscopic techniques has given rise to widespread enthusiasm for endoscopy, and the great majority of neurosurgeons has accepted neuroendoscopy as a neurosurgical procedure for a wide range of ventricular diseases [1, 2, 3, 4, 5], as all previous reports have emphasized the speed, safety and simplicity of this procedure [2, 4]. Nevertheless, even in very experienced hands, some complications have been reported [1, 2, 3, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even in very experienced hands, some complications have been reported [1, 2, 3, 5]. The complication rate associated with endoscopic techniques is low however and varies from 4.1 to 20% [1, 5, 6].…”
Section: Introductionmentioning
confidence: 99%